The economics of commercial swine production in Iloilo - De Los Reyes, John Jofre I. (2003.)
This study determined the economic performance and cost structure of commercial swine production in Iloilo. This study also described the swine production practices, production cycle identified different problems encountered in the operation., There were 21 respondents in the study. They were based on the updated list of commercial swine raisers in Iloilo given by Bureau of Agricultural Statistics. Cross-sectional data were used in this study. The results of the study showed that on the average sows farrowed twice a year and piglets were reared for fattening was 1,435 piglets. The daily weight gain of the fattened pigs was 467 grams per day. The total feed cost per fattener was P 2,230.64 and the total feed consumption of the fatteners was 220.75 kilograms of feed were needed to gain a kilogram of weight. Cost and return analysis showed that on the average, initial farm investments amounted to P 4,595,395.00. The annual cost of the commercial piggery farms incurred an average of P 6,514,603.66. The annual total fixed cost per commercial piggery farm was P 1,236,342.79. Total variable costs of the farms recorded an annual average of P 4,903,424.96. The annual total revenue of the farms amounted to P 7,904,250.00. The commercial piggery farms earned an average economic profit of P 1,389,646.34. The economic profit per sow and per fattener earned totaled P 17,815.98 and 968.39, respectively. On the other hand, gross profit of the commercial piggery farms was P 3,000,825.0. The rate of return on investment of commercial piggery farms was 30.24%. The rate of return on total operating costs was 28.34% . The ratio of economic profit to total revenue was 17.58% and the payback period was 3.31 years. Swine industry in Iloilo enjoyed net returns that were 2.44 and 4.16 times higher than cattle and carabao industry, respectively.
Research Project (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Swine Production